Holistic Management of Mutilated Dentition - Vidyalakshmi Chandrasekar; Ahila Singaravel Chidembaranathan; Muthukumar Balasubramanium (Faculty of Dentistry, Universitas Trisakti, 2020)
Background: Worn dentition has become a common and crucial issue, especially in the older generation. Beyond esthetics, functional diminution can create a serious impact on the overall well-being of the individual. The etiology of the worn dentition can be multifactorial; therefore, the treatment approach should be systematic and must not only address the existing problem but also prevent any recurrence. Case Report: Rehabilitation of a patient with worn dentition requires proper clinical, radiographic examination and recording of the occlusal vertical dimension (OVD). In this case report, a 65-year-old male patient presented with worn out and missing teeth in his upper and lower jaws. An arbitrary face-bow transfer was conducted, and the diagnostic casts were articulated. A mock full contoured wax up with a raised OVD of approximately 4 mm was completed. After 3 months of interocclusal splint therapy with the raised OVD, temporary restoration was cemented. After a follow-up period of 3 months, when the patient was devoid of any signs and symptoms, permanent restorations fabricated using computer-aided design and computer-aided manufacturing were cemented. An interocclusal splint was provided to preserve the restorations. Conclusion: Rehabilitating patients with worn dentition involves careful decision-making during the diagnosis as it will direct the entire treatment sequence. This case report and the resulting steps involved might serve as guidelines for other clinicians while treating similar patients